Comparative analysis of weight product and electre methods in determining the quality of assessment Teacher performance - Febrianto Febrianto; Herlina Latipa Sari; Eko Suryana (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2023)
SD Negeri 4 Bengkulu Selatan has been conducting teacher performance appraisals every year based on criteria categorized into 4 competencies, namely Pedagogic, Personality, Social, and Professional. However, the assessment process is still carried out manually so that errors often occur in providing the final results in the assessment of teacher performance and also takes a long time. Analysis of the comparison of the Weight Product and Electre methods in determining the quality of teacher performance appraisals at SD Negeri 4 Bengkulu Selatan was made using the Visual Basic .Net programming language and SQL Server 2008r2 database. This application can help make it easier for schools to give performance appraisals to each teacher and find out the quality of teacher performance appraisals each year at SD Negeri 4 Bengkulu Selatan based on the Weight Product and Electre Methods. From the comparison results of the Weight Product Method and the Electre Method, it can be concluded that based on the process time, the Weight Product Method has a faster time than the Electre Method, and based on the final results of the assessment, the Weight Product Method and the Electre Method have the same final results.